Reduced fire severity offers near-term buffer to climate-driven declines in conifer resilience across the western United States - Davis, Kimberley T., author; Robles, Marcos D., author; Kemp, Kerry B., author; Higuera, Philip E., author; Chapman, Teresa, author; Metlen, Kerry L., author; Peeler, Jamie L., author; Rodman, Kyle C., author; Woolley, Travis, author; Addington, Robert N., author; Buma, Brian J., author; Cansler, C. Alina, author; et al. (Colorado State University. Libraries, 2023)
Increasing fire severity and warmer, drier postfire conditions are making forests in the western United States (West) vulnerable to ecological transformation. Yet, the relative importance of and interactions between these drivers of forest change remain unresolved, particularly over upcoming decades. Here, we assess how the interactive impacts of changing climate and wildfire activity influenced conifer regeneration after 334 wildfires, using a dataset of postfire conifer regeneration from 10,230 field plots. Our findings highlight declining regeneration capacity across the West over the past four decades for the eight dominant conifer species studied. Postfire regeneration is sensitive to high-severity fire, which limits seed availability, and postfire climate, which influences seedling establishment. In the near-term, projected differences in recruitment probability between low- and high-severity fire scenarios were larger than projected climate change impacts for most species, suggesting that reductions in fire severity, and resultant impacts on seed availability, could partially offset expected climate-driven declines in postfire regeneration. Across 40 to 42% of the study area, we project postfire conifer regeneration to be likely following low-severity but not high-severity fire under future climate scenarios (2031 to 2050). However, increasingly warm, dry climate conditions are projected to eventually outweigh the influence of fire severity and seed availability. The percent of the study area considered unlikely to experience conifer regeneration, regardless of fire severity, increased from 5% in 1981 to 2000 to 26 to 31% by mid-century, highlighting a limited time window over which management actions that reduce fire severity may effectively support postfire conifer regeneration.
Keywords: climate change; wildfire; ecological transformation; post-fire regeneration; vegetation transition